Take Control of iCloud, 7th Edition - Kissell, Joe (Take Control Books, 2020)
Understand iCloud's capabilities and limitations, and put its key features to good use! Version 7.0, Updated 8/10/2020 Apple's iCloud service is highly useful, but it can also create headaches for the average user. In Take Control of iCloud, Seventh Edition , Joe Kissell explains how to avoid frustrations and make iCloud work for you across all your devices. iCloud is a simple idea in theory-access to all your data on all your devices, via the cloud-that can become complicated when put into practice. Instead of wasting time fiddling with iCloud, when there are many other more important things to be done with the information it contains, learn how to minimize frustrations with Take Control of iCloud, Seventh Edition ! Whether you want a quick tip or a deep dive into the inner workings of iCloud, you'll find what you need in this best-selling book by Mac expert Joe Kissell. Start by learning what iCloud can do, how it differs from other cloud services, and how best to set it up on Macs, iOS and iPadOS devices, Apple TVs, and Windows-based PCs. Then, move on to finding out the key aspects-and hidden gotchas-of iCloud's core features, including: Photo features: iCloud Photog, My Photo Stream, and iCloud Photo Sharing Family Sharing iTunes Match and iCloud Music Library iCloud Drive (including folder sharing and the Files app for iOS and iPadOS) Mail and Mail Drop Contacts, Calendars, Reminders, and Notes iCloud Keychain the iCloud website Location features: Find My Device , Find My Friends, and the Find My app Two-factor authentication Activation lock Backing up and restoring data This edition not only covers the changes to iCloud in macOS 10.15 Catalina, iOS 13, and iPadOS 13 but is also up to date (as of August 2020) with macOS 11 Big Sur, iOS 14, and iPadOS 14. It also continues to cover macOS 10.14 Mojave and iOS 12, but drops coverage of earlier operating system versions.